2007
DOI: 10.1300/j233v06n02_05
|View full text |Cite
|
Sign up to set email alerts
|

Potential Risk Factors for Injecting Among Mexican American Non-Injecting Heroin Users

Abstract: SUMMARYThis study examines potential risk factors for resuming and transitioning to injecting among a prospective cohort of 300 Mexican American non-injecting heroin users (NIUs) with distinct injecting histories (i.e., never vs. former injectors). Overall. findings revealed NIUs with an injecting history are more likely to be at greater risk for resuming injecting practices. Of interest, scoring high on acculturation decreased the risk of being a former injector. The present analysis supports previous researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, the pervasive availability of heroin coupled with the thriving subculture of the tecato lifestyle demonstrates how social context facilitated initiation of heroin, a drug that most would continue using all of their lives. The men in this study grew up in a setting in which heroin was highly visible and readily available, a product of the historic segregation of Latinos into ethnic vice districts throughout the Southwest and other Mexican settlement areas in the United States (Valdez, Neaigus, & Cepeda, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…However, the pervasive availability of heroin coupled with the thriving subculture of the tecato lifestyle demonstrates how social context facilitated initiation of heroin, a drug that most would continue using all of their lives. The men in this study grew up in a setting in which heroin was highly visible and readily available, a product of the historic segregation of Latinos into ethnic vice districts throughout the Southwest and other Mexican settlement areas in the United States (Valdez, Neaigus, & Cepeda, 2007). …”
Section: Resultsmentioning
confidence: 99%
“…Thus, when the socio-ecological environment sees heroin use as normative, cultural values can become negatively directional. Valdez and colleagues found that, specific to heroin use, family-based networks ( familismo and personalismo ) provided for “a paradoxical position of having the highest and lowest propensity for engaging in risk behaviors” and that machismo plays a role in the initiation, cessation, and attempts toward cessation of heroin among Mexican Americans (Valdez, Kaplan, & Cepeda, 2006; Valdez, Kaplan, & Curtis, 2007; Valdez, Neaigus, & Cepeda, 2007; Valdez et al, 2008). More importantly, Casavantes (1976) and Bullington (1977) identified and described examples of these dichotomous associations between cultural values and heroin use going back at least three decades and these trends continue today.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While these studies have yielded important insights into motivations, risk factors, and drug-specific experiences related to uptake of injection (Ahamad et al, 2014; Bryant and Treloar, 2007; Chami et al, 2013; Cheng et al, 2006; Day et al, 2005; Doherty et al, 2000; Eaves, 2004; Feng et al, 2013; Fuller et al, 2005, 2001, 2003, 2002; Goldsamt et al, 2010; Kermode et al, 2009, 2007; Lankenau et al, 2007, 2012, 2010; Lloyd-Smith et al, 2009; Mackesy-Amiti et al, 2013; Miller et al, 2011, 2006; Novelli et al, 2005; Ompad et al, 2005; Roy et al, 2010, 2011, 2003; Sherman et al, 2005; Small et al, 2009; Trenz et al, 2012; Valdez et al, 2007, 2011; Werb et al, 2013; Wood et al, 2008; Young and Havens, 2011; Young et al, 2014), they have not examined injection initiation extensively from the viewpoint of established PWID who often assist non-injectors into injection drug use. We know little about behaviors among established PWID that may socialize or promote uptake of injection drug use among non-injectors.…”
Section: Introductionmentioning
confidence: 99%